Clients fidelization strategies for the internet service - Pesantez Chiriboga, Iván Fernando (2018)
This research proposes customer loyalty strategies for the Internet service, based on important concepts of service marketing, consumer behavior and customer loyalty; Supporting the proposal through market research whose methodology and results are exposed to be considered as a basis for the formulation of the proposal and its corresponding actions for the aforementioned services. To achieve the results, qualitative research tools were used, among them: in-depth interviews with experts in the aforementioned services and, as part of the quantitative research and based on a probabilistic sampling, random surveys were conducted to users of the different suppliers. of internet services. The results of this research generated management strategies and indicators that could constitute a basis for a customer loyalty plan, in order to avoid the abandonment or flight of customers to the company, keeping in mind that the customer is the reason to be of any organization.